Penerapan Metode Pembelajaran Berbasis Proyek untuk Meningkatkan Kreativitas Siswa SD Negeri 1 Sukarami Kecamatan Tanjung Lubuk - Syarwani Ahmad; Nuril Furkan; Syarwani Syarwani (CV. Ulil Albab Corp, 2026)
Project-based learning at SD Negeri 1 Sukarami is implemented through planning activities, group work, and the creation of tangible products that encourage student creativity. However, its implementation still faces limitations in facilities, time, and teacher readiness, which necessitates various collaborative efforts between the school and parents. This study employed a qualitative approach with a descriptive method. The research subjects included the principal, school supervisors, classroom teachers, students, and the school committee. Data were collected through in-depth interviews, observations, and documentation. Data analysis was conducted through the stages of data reduction, data display, and conclusion drawing. The results indicate that the implementation of the Project-Based Learning (PjBL) method at SD Negeri 1 Sukarami has been carried out in accordance with the main principles of Project-Based Learning, namely student-centered learning through project planning, group-based implementation, the creation of tangible products, and the presentation of learning outcomes. The application of this method has a positive impact on student creativity, as evidenced by increased student confidence in expressing ideas, the emergence of diverse ideas and creative products, the development of divergent thinking skills (fluency, flexibility, originality, and elaboration), as well as increased student motivation and enthusiasm in participating in learning activities.Nevertheless, this study also identified several obstacles, including limited facilities and infrastructure, limited instructional time, differences in teachers’ readiness to implement PjBL, variations in students’ abilities and confidence in group work, and uneven parental support. To address these challenges, the school has implemented various collaborative solutions, including making PjBL a school priority program, providing flexibility in learning time, conducting teacher supervision and mentoring, utilizing simple and locally available materials, and strengthening cooperation with parents and the school committee.